2001
DOI: 10.1021/ar000140d
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized Lyotropic Liquid Crystal Assemblies for Materials Applications

Abstract: The development of functional materials with nanometer-scale architectures and the effect of these architectures on their chemical and physical properties are currently of great interest in materials design. Polymerizable lyotropic liquid crystal (LLC) assemblies provide a facile entry into this area by allowing one to fix the inherent order in these systems using covalent bonds to create robust, nanostructured materials. The use of the cross-linked inverted hexagonal phase in templated nanocomposite formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
200
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(204 citation statements)
references
References 52 publications
2
200
0
2
Order By: Relevance
“…4 Many concepts and synthetic approaches have been developed to prepare macromolecules with various architectures and topologies, including dendrimers [5][6][7][8] and hyperbranched polymers, 9 -15 supramolecular polymers, 16 -21 cylindrical and spherical polymers, [22][23][24] polymers having folded structures, [25][26][27] molecular wires, 28 -30 metal-core polymers, 31,32 and polymeric nanostructures. [33][34][35] Vinyl polymers are an important category of synthetic materials, with millions of tons produced every year for broad applications such as fibers, plastics, and elastomers. 36 Most vinyl polymers are synthesized by the addition polymerization of vinyl monomers.…”
Section: Introductionmentioning
confidence: 99%
“…4 Many concepts and synthetic approaches have been developed to prepare macromolecules with various architectures and topologies, including dendrimers [5][6][7][8] and hyperbranched polymers, 9 -15 supramolecular polymers, 16 -21 cylindrical and spherical polymers, [22][23][24] polymers having folded structures, [25][26][27] molecular wires, 28 -30 metal-core polymers, 31,32 and polymeric nanostructures. [33][34][35] Vinyl polymers are an important category of synthetic materials, with millions of tons produced every year for broad applications such as fibers, plastics, and elastomers. 36 Most vinyl polymers are synthesized by the addition polymerization of vinyl monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, physical stabilization of self-assembled nanoobjects through covalent bonds is an important subject for practical applications of supramolecular chemistry. [51][52][53] Along this line, we designed HBC amphiphile 4 bearing allylic functionalities at the termini of the oxyalkylene chains. 54 Since the hydrophilic chains cover both inner and outer surfaces of graphitic nanotubes (Figure 10), we initially expected that acyclic diene metathesis (ADMET) 55 of preformed nanotubes of 4 ( Figure 15) can lead to the formation of surfacepolymerized nanotubes (Figure 16).…”
Section: Electrical Properties Of Self-assembled Graphitic Nanotubesmentioning
confidence: 99%
“…[15,16] The first development of an organic nanoporous material with 1D-aligned nanochannels was reported by Gin and co-workers. [17][18][19][20] They demonstrated that lyotropic liquid crystals (LCs) could be aligned on a macroscopic scale to form a well-defined nanoporous material for water filtration applications. Feringan et al, [21,22] Kraft et al, [23] Kishikawa et al, [24] and Lee et al [25] have shown examples of columnar LC complexes between benzoic acid derivatives and different kinds of template molecules that form multiple mesophases depending on the length of the alkyl tails applied to the benzoic acid derivatives.…”
mentioning
confidence: 99%